Above- and belowground trait linkages of dominant species shape responses of alpine steppe composition to precipitation changes in the Tibetan Plateau. (31st January 2021) - Zheng, Zhi; Zhang, Yue; Zhang, Shihu; Ma, Qun; Gong, Dajie; Zhou, Guoying
Abstract: Aims: Human activities and global changes have led to alterations in global and regional precipitation regimes. Despite extensive studies on the effects of changes in precipitation regimes on plant community composition across different types of grassland worldwide, few studies have specifically focused on the effects of precipitation changes on high-altitude alpine steppe at community and plant species levels in the Tibetan Plateau. Methods: We investigated the effects of growing-season precipitation changes (reduced precipitation by 50%, ambient precipitation, enhanced precipitation by 50%) for 6 years on plant community composition in an alpine steppe of the Tibetan Plateau by linking above- to belowground traits of dominant species. Important Findings: We found that reduced precipitation shifted community composition from dominance by bunchgrass (primarily Stipa purpurea ) to dominance by rhizomatous grass (primarily Leymus secalinus ). Roots and leaf traits of L. secalinus and S. purpurea differed in their responses to reduced precipitation. Reduced precipitation enhanced root vertical length and carbon (C) allocation to deep soil layers, and decreased the leaf width in L. secalinus, but it did not change the traits in S. purpurea . Moreover, reduced precipitation significantly enhanced rhizome biomass, length, diameter and adventitious root at the rhizome nodes in L. secalinus . These changes in traits may render rhizomatous grass greater competitive during drought stress. Therefore, our findings highlight important roles of above- and belowground traits of dominant species in plant community composition of alpine steppe under precipitation change.